Uma contribuição ao estudo da programação linear - Silva Junior, Carlos Alberto da (2008)
The Linear Programming is quite useful to obtain optimal solutions for problems related to several areas of science, such as, industrial engineering, food industry, health science, mining, transport, among others. This work makes a review about linear programming, producing a didactic-scientific text that presents a consistent theoretical base of the main concepts of linear programming. In this study three computer codes, Lindo, Linprog and Mosek, are compared considering the computacional time, the number of iterations, the optimal values of the objective function and the design variables. The problem of the optimal planning of goods transportation and the optimization of water distribution networks are formulated and solved, by comparing the values obtained with the three studied codes and also with results found in the literature.